EveOut: an event-centric news dataset to analyze an outlet's event selection patterns - Swati, Swati; Mladenić, Dunja; Erjavec, Tomaž (Informatica, 2021)
Automation of computational models to study the structure of events and their value to news outlets is an effective way to understand event-outlet relationships. However, the scarcity of publicly available, comprehensive event-centric news datasets restricts the implementation of such models. To overcome this bottleneck, we collected seventeen months of event data using Event Registry to generate EveOut, a publicly available event-centric news dataset. To conduct statistical analysis, we first select five English-language and three in Slovenian-language news outlets. We then retrieved all the events covered by them and used it to document the prevalence of geographical, temporal, categorical, and several other aspects of the event selection bias by these outlets. We illustrate the significance of our dataset in the field of digital humanities by identifying a motivating use case. The dataset is publicly available from the dedicated website http://cleopatra.ijs.si/EveOut/, which provides a detailed description of the fields, usage information, and a link to the GitHub repository.